2022
DOI: 10.1051/0004-6361/202142264
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and molecular gas from the epoch of reionisation down to redshift 2

Abstract: Context. Cosmic gas makes up about 90% of the baryonic matter in the Universe and H2 molecule is the most tightly linked to star formation. Aims. In this work we study cold neutral gas, its H2 component at different epochs, and corresponding depletion times. Methods. We perform state-of-the-art hydrodynamic simulations that include time-dependent atomic and molecular non-equilibrium chemistry coupled to star formation, feedback effects, different UV backgrounds presented in the recent literature and a number o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 226 publications
(300 reference statements)
3
29
0
Order By: Relevance
“…Walch et al 2015;Rathjen et al 2021;Hu et al 2021), isolated galaxies (e.g. Richings & Schaye 2016;Hu et al 2016;Lahén et al 2019), and more recently in cosmological simulations (Maio et al 2022). These studies have shown that nonequilibrium chemistry e.g.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Walch et al 2015;Rathjen et al 2021;Hu et al 2021), isolated galaxies (e.g. Richings & Schaye 2016;Hu et al 2016;Lahén et al 2019), and more recently in cosmological simulations (Maio et al 2022). These studies have shown that nonequilibrium chemistry e.g.…”
Section: Discussionmentioning
confidence: 92%
“…These studies have shown that nonequilibrium chemistry e.g. heavily influences the H 2 mass fraction at low metallicities (Hu et al 2021), affect the chemical make-up of outflows (Richings & Schaye 2016) and more accurately repro-duce cosmological H 2 mass densities of observations (Maio et al 2022) The global 𝑓 (𝑁 H 2 ) and that of individual main-sequence starforming galaxies give first indications that its shape could be related to the gas distribution within gas disks. Exponential gas distributions have not only been observed in disk galaxies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first detection of the absorption in this line at z = 15 − 20 was announced by the EDGES 1 team a few years ago (Bowman et al 2018;Hills et al 2018). Other sources of important information about the formation of the first stars and galaxies are the first molecules, which absorb the cosmic microwave background radiation (CMBR) in their rovibrational transitions in cold baryonic matter clouds, while emitting additional radiation in hot ones or resonantly scattering it in moving clouds (Dubrovich 1977;Maoli et al 1994Maoli et al , 1996Kamaya & Silk 2002;Ripamonti et al 2002;Kamaya & Silk 2003;Omukai & Kitayama 2003;Mizusawa et al 2004Mizusawa et al , 2005Dubrovich et al 2008;Liu et al 2019;Novosyadlyj et al 2020;Maio et al 2022). Unfortunately, predictions of the amplitudes of such distortions of CMBR are at the level of microkelvins and too low for their detection by current telescopes.…”
Section: Introductionmentioning
confidence: 99%